COMMUNITY ENTREPRENEURSHIP DEVELOPMENT STRATEGY THROUGH THE HOME INDUSTRY OF MAKING RED GINGER WEDANG, KALAMPANGAN VILLAGE, PALANGKA RAYA CITY - Yesninopy (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2022)
The purpose of this study was to find out how the strategy of developing community entrepreneurship through the home industry of making red ginger wedang both seen from its strengths and weaknesses in the village of Kalampangan, Palangka Raya city. The method used was using a qualitative method that produced descriptive data. The research subjects were managers and employees. The instruments used were observation/observation, in-depth interviews by asking questions and documentation. The results showed that Rossemi Home industry is a household business that produces red ginger wedang, this home industry operates in Kalampangan Village, Palangka Raya City The advantages or advantages of the Rossemi home industry are in terms of the variety of flavors that are produced in various flavors which other home industries do not have. In addition, the production of ginger wedang uses high quality ginger raw materials, sugar so as to produce quality ginger wedang products as well. However, the weakness of this home industry is that the technology used to produce red ginger wedang is still manual, so time is limited if there are many orders from consumers.